Program Keagamaan Berbasis Masyarakat Di Desa Tanah Periuk Kecamatan Muara Beliti Kabupaten Musi Rawas - Manora, Hecsa; Ref’ati, Ruvi; Aliyah, Fadilatul; Salsabilah, Dwi Putri; Sanjaya, Arta; Siswanto, Siswanto (El-Ghiroh : Jurnal Studi Keislaman, 2022)
The Kukerta Mandiri program in the community has the aim of increasing and developing motivation in the Tanah Periuk Village community. The targets that are expected to be achieved include: the need for religious knowledge for students is maximally fulfilled, cleanliness in the Nurul Iman Mosque environment is always maintained, invites the surrounding community to see business opportunities and manages agricultural products into small and medium enterprises, health of the elderly in the village. Tanah Periuk can be optimally maintained and monitored, the success of character education for students and for growing national unity and integrity as the main capital for the nation's children who need the important role of the family in forming patterns of thought and behavior for a sense of nationalism, as well as improving the mental and character of participants. better education, increase faith, piety and foster social sensitivity. The method of implementing this activity is education and practice, discussion, pilot and mentoring, sustainable development, adapting to the surrounding community and participating in every activity held by the surrounding community in Tanah Periuk Village. Some of the results achieved in this activity include the religious understanding of students who are already good, the environment around the Nurul Iman mosque is clean, manages the agricultural produce of the surrounding community into small businesses, students are diligent in participating in the flag ceremony, and the mental and character of students who are better.